COMPARATIVE ANANALYSIS OF INCOME OF SMALLHOLDER CEREALS AND LEGUMES CROP ENTERPRISES IN NASARAWA STATE - NIGERIA - Sumaka, Emmanuel Chahul (International Journal of Agriculture, 2017)
Purpose: The purpose of this study was to assess comparative analysis of income of smallholder cereals and legumes crop enterprises in Nasarawa state - Nigeria Method: Purposive, multi-stage and stratified sampling techniques were employed to obtain data on 174 respondents, using structured questionnaire for the study. Data collected were analyzed using descriptive and inferential statistics. Results: Results show that majority of the farmers were male (62.1%). Farmers were in their active age, with mean age of 39 years for both cereals and legumes. Mean gross margin per hectare was N72, 676 and N70, 446 for cereals and legumes respectively. Farm size, labour, seeds, pesticides and fertilisers were the inputs that significantly influenced the output of the farmers with positive F values of 19.018 and 29.017 for cereals and legumes respectively. The results from t-test revealed that there is no significant difference between the incomes of cereals (119,087) and legumes (118,590) farmers at 5 percent level of probability. Age of cereal farmers (4.812)*, age (3.332)*, output (2.019)* for legume farmers respectively were the socioeconomic factors that significantly influenced incomes of respondents in the study area at 5 percent level of probability with significant F value (1.17) at 5% level of probability. Lack of improved seed variety, land tenure system and high cost of inputs were the major constraints faced by the farmers in the study area. Policy recommendation: It is recommended that effective input delivery system, improved rural transportation system, adult education and training of the farmers be carried out to build up the capacity base of rural producers of cereals and legumes in the study area and Nigeria at large.